(untitled) (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Despite the variety of obturation techniques available, no single method has been established as the ideal approach for obturating primary tooth root canals. The purpose of the study is to compare the success rate of pulpectomy in primary teeth using different obturation techniques. Aim of the study: The aim of the study is to compare the success rate of pulpectomy in primary teeth using different obturation techniques. Methods: This prospective comparative study was conducted at the Department of Dentistry, Bangladesh Shishu Hospital & Institute, from January 2023 to January 2024. Forty healthy children (aged 4–8 years) with 60 primary molars requiring pulpectomy were randomly assigned to three obturation groups (Disposable Syringe, Lentulo Spiral, Past inject System; n=20 each). Data were analyzed using SPSS version 25.0, with significance set at p < 0.05. Results: Among 60 primary molars, the Past inject System showed the highest success rates—clinical (95%), radiographic (95%), and overall (90%)—with the lowest complications (10% discomfort, 5% swelling, 0% retreatment). Lentulo Spiral and Disposable Syringe had lower success (80–90%) and higher complications (up to 20%). Differences were not statistically significant (p > 0.05). Baseline characteristics were comparable. Conclusion: The Past inject System demonstrated the highest success and lowest complications, indicating it may be the preferred obturation technique for pulpectomy in primary molars. J Shaheed Suhrawardy Med Coll 2024; 16(1): 2-6